2004
DOI: 10.1080/15287390490514651
|View full text |Cite
|
Sign up to set email alerts
|

Mechanism of Antifertility in Male Rats Treated With 3-Monochloro-1,2-Propanediol (3-McPd)

Abstract: 3-Monochloro-1,2-propanediol (3-MCPD) is a food contaminant that is often found in foods containing acid-hydrolyzed (AH) protein, like seasonings and savory food products. The purpose of the present study was to investigate the effects of 3-MCPD on male fertility, sperm, and hormonal levels and its antifertility mechanism. In vivo male fertility testing was performed to observe the adverse effects of 3-MCPD on the functioning of the male reproductive system and pregnancy outcome. 3-MCPD (0.01-5 mg/kg) was admi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
21
0
5

Year Published

2007
2007
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(29 citation statements)
references
References 25 publications
3
21
0
5
Order By: Relevance
“…Interference with glycolysis due to an inhibition of GAPDH activity by b-chlorolactaldehyde, a metabolite of 3-MCPD and 3-MCPD esters, has been reported by different groups (JECFA, 2002;Jones and Porter, 1995;Mohri et al, 1975). Earlier studies postulated that 3-MCPD treatment reduces sperm motility, thus massively hampering fertilization (Kwack et al, 2004;Miki et al, 2004). Apart from its function in energy metabolism, GAPDH is also capable of altering cytoskeletal structure and interacts with tubulin and actin in microtubule bundling and actin polymerization (Sirover, 2011).…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…Interference with glycolysis due to an inhibition of GAPDH activity by b-chlorolactaldehyde, a metabolite of 3-MCPD and 3-MCPD esters, has been reported by different groups (JECFA, 2002;Jones and Porter, 1995;Mohri et al, 1975). Earlier studies postulated that 3-MCPD treatment reduces sperm motility, thus massively hampering fertilization (Kwack et al, 2004;Miki et al, 2004). Apart from its function in energy metabolism, GAPDH is also capable of altering cytoskeletal structure and interacts with tubulin and actin in microtubule bundling and actin polymerization (Sirover, 2011).…”
Section: Discussionmentioning
confidence: 94%
“…At higher doses of 3-MCPD of >10e20 mg/kg body weight per day, alterations in sperm morphology and epididymal lesions are additionally observed in rats (Jones, 1983). Moreover, spermatotoxic effects of 3-MCPD are suggested to be mediated by reduced H1-ATPase expression and effects on protein kinase A signaling, leading to a disruption of sperm maturation and reduced sperm motility (Kwack et al, 2004;Zhang et al, 2012). Nevertheless, further studies are necessary to elucidate the molecular consequences of 3-MCPD testicular toxicity and its esters.…”
Section: Introductionmentioning
confidence: 93%
“…3-MCPD is considered to cause toxicity in several tissues and spermatozoa through inhibition of GAPDH and therefore glycolysis with energy depletion as result (Ford and Waites, 1982;Kwack et al, 2004;Skamarauskas et al, 2007). This mechanism may be involved also in neurons because cytotoxicity of 3-MCPD in primary mouse neocortical cells was associated with a drop in cellular ATP, and both decrease in ATP and cell death were ameliorated by addition of pyruvate to the culture medium (Sheline and Choi, 1998).…”
Section: Mode Of Action For Neurotoxicitymentioning
confidence: 99%
“…It has been clearly shown that the toxicity of 3-CPD to spermatozoa (Jones and Porter, 1995;Kwack et al, 2004) is attributable to catalytic inhibition of glyceraldehyde-3-phosphate dehydrogenase (GAPDH), a polyfunctional protein (Sirover, 1997) that plays a key role in glycolysis. In addition, it has been shown in neuronal cultures that 3-CPD causes cell death and an increase in the concentration of dihydroxyacetone phosphate (which is in isomeric equilibrium with glyceraldehyde-3-phosphate, G3P), and that neuronal death could be antagonised by addition of pyruvate, the product of GAPDH (Sheline and Choi, 1998).…”
Section: Introductionmentioning
confidence: 99%